2023
DOI: 10.3390/foods12051071
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Volatile Organic Compounds in Milk during Heat Treatment Based on E-Nose, E-Tongue and HS-SPME-GC-MS

Abstract: Volatile organic compounds (VOCs) make up milk flavor and are essential attributes for consumers to evaluate milk quality. In order to investigate the influence of heat treatment on the VOCs of milk, electronic nose (E-nose), electronic tongue (E-tongue) and headspace solid-phase microextraction (HS-SPME)–gas chromatography–mass spectrometry (GC-MS) technology were used to evaluate the changes in VOCs in milk during 65 °C heat treatment and 135 °C heat treatment. The E-nose revealed differences in the overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Prior research (Petrucci et al, 2016;Jung et al, 2023) indicates that heating provided molecular energy to break atom-to-atom bonds, resulting in smaller molecules or volatiles, but it also led to volatile degradation (Yuan et al, 2023). Moreover, found that the pH of the solution affected the volatility of the compounds through two processes: 1) decomposition, in which a low or high pH caused some compounds to break down into smaller, more volatile molecules, and 2) acid and base reactions, which result in charged ions, which are less volatile than neutral molecules.…”
Section: Overall Volatile Profilementioning
confidence: 99%
“…Prior research (Petrucci et al, 2016;Jung et al, 2023) indicates that heating provided molecular energy to break atom-to-atom bonds, resulting in smaller molecules or volatiles, but it also led to volatile degradation (Yuan et al, 2023). Moreover, found that the pH of the solution affected the volatility of the compounds through two processes: 1) decomposition, in which a low or high pH caused some compounds to break down into smaller, more volatile molecules, and 2) acid and base reactions, which result in charged ions, which are less volatile than neutral molecules.…”
Section: Overall Volatile Profilementioning
confidence: 99%
“…The E-tongue method was used to evaluate the differences in the taste attributes of loquat under different preservation methods [48]. The basic sensory taste indices were presented as radar images (Figure 10A).…”
Section: E-tongue Analysismentioning
confidence: 99%
“…Some volatile compounds, including protonated monomers (M) and proton-bound dimers (D). 37 Most of these volatile chemicals belong to distinct chemical categories, such as esters (18), ketones (14), aldehydes (18), alcohols (12), ethers (1), furans (1), and unidentified compounds (10).…”
Section: Gc-ims Analysis Topographic Plotsmentioning
confidence: 99%
“…The electronic nose (E‐nose) is a bionic instrument that mimics the human olfactory cells. Using an array of sensors, an E‐nose can quickly differentiate distinct aroma profiles and provide overall odour descriptions 12 . However, few studies have investigated aroma changes in fermented blueberry juice by combining GC–IMS and E‐nose analyses.…”
Section: Introductionmentioning
confidence: 99%